Fractalkine/CX3CR1 signaling during neuropathic pain - Clark, Anna K.; Malcangio, Marzia (Frontiers in Cellular Neuroscience, 2014)
Chronic pain represents a major problem in clinical medicine. Whilst the acute pain that is associated with tissue injury is a protective signal that serves to maintain homeostasis, chronic pain is a debilitating condition that persists long after the inciting stimulus subsides. Chronic neuropathic pain that develops following damage or disease of the nervous system is partially treated by current therapies, leaving scope for new therapies to improve treatment outcome. Peripheral nerve damage is associated with alterations to the sensory neuroaxis that promote maladaptive augmentation of nociceptive transmission. Thus, neuropathic pain patients exhibit exaggerated responses to noxious stimuli, as well as pain caused by stimuli which are normally non-painful. Increased nociceptive input from the periphery triggers physiological plasticity and long lasting transcriptional and post-translational changes in the CNS defined as central sensitization. Nerve injury induces gliosis which contributes to central sensitization and results in enhanced communication between neurons and microglial cells within the dorsal horn. Thus, identification of mechanisms regulating neuro-immune interactions that occur during neuropathic pain may provide future therapeutic targets. Specifically, chemokines and their receptors play a pivotal role in mediating neuro-immune communication which leads to increased nociception. In particular, the chemokine Fractalkine (FKN) and the CX3CR1 receptor have come to light as a key signalling pair during neuropathic pain states.